“Low-altitude + Culture Tourism” Creates New Growth Points for Urban Cultural Consumption (Contemporary Education and Teaching Research, 2025)
With the vigorous development of the low-altitude economy, the deep integration of low-altitude flight technology and the culture tourism industry has given rise to the new consumption scenario of “low-altitude + culture tourism,” which has become an important engine for promoting the upgrading of urban cultural consumption. Based on the background of the transformation of urban cultural consumption, this paper systematically analyzes the mechanisms by which low-altitude flight technology expands the space for cultural consumption, restructures the supply of culture tourism products, and stimulates high-quality consumption. It proposes that “low-altitude + culture tourism” reshapes urban culture tourism scenarios and consumption patterns by integrating immersive experiences with cultural narratives. At the same time, the paper reveals key problems in the current development of “low-altitude + culture tourism,” such as the lag in airspace management mechanisms, incomplete infrastructure, single product supply, and insufficient policy support. On this basis, the paper puts forward suggestions for optimizing the opening of low-altitude airspace, improving the layout of infrastructure, deepening the development of cultural IPs, and perfecting policy and market mechanisms. The study believes that “low-altitude + culture tourism” is not only expected to lead the structural upgrading of urban cultural consumption but will also play a positive role in promoting the intelligent development of the culture tourism industry and enhancing urban cultural soft power.